Drug repurposing of fostamatinib against cancer via potential cytotoxicity and immune checkpoint regulation - Hu, Maoqiong; Yin, Renyi; Deng, Kaifeng; Xu, Ning (Frontiers in Immunology, 2025)
Acute myeloid leukemia (AML), originating from myeloid hematopoietic stem/progenitor cells, is a malignant hematological disorder. Resistance to current treatments, especially in FLT3-ITD AML cases, urgently demands the development of novel therapeutics. In this study, we pinpointed fostamatinib, an orally delivered small molecule SYK inhibitor for chronic immune thrombocytopenia (ITP), as a promising candidate for drug repurposing. It effectively inhibited FLT3-ITD+ AML cell proliferation and induced leukemic cell apoptosis. Network pharmacology analysis further deciphered the associated pharmacological mechanism related to the PI3K-AKT signaling pathway. Moreover, fostamatinib downregulated the expression of immune checkpoints such as PD-L1 and CD47. Overall, this study provided a conceptual foundation for evaluating the advantages of drug repurposing in AML drug development.